KUALITAS SENSORIS DAGING ITIK AFKIR DENGAN LAMA PEMBERIAN TEPUNG DAUN ASAM GELUGUR (GARCINIA ANTROVIRIDIS) YANG BERBEDA DALAM RANSUM KOMERSIL - hardiyanto, Rico; Dewi Wahyuni; ELis Dihansih (Jurnal Peternakan Nusantara, 2021)
Compared to other animals, duck has some superiority as it is relatively more resistant to diseases and easier to raise. Garcinia leaf contains high hydroxycitric acid which is an organic acid known to have antilipidemic and antiobesity properties. This study was aimed at assessing the effects of the inclusion of garcinia leaf meal in rations in different length of time on sensory quality of meat of culled ducks. The study was conducted at the poultry farm of Department of Animal Science, Djuanda University, Bogor in 30 June to 4 August 2019. Sixteen culled female ducks were used in a completely randomized design with 4 treatments and 4 replicates. Four ducks were allocated to each treatment. Treatments consisted of the inclusion of 0% garcinia leaf meal in rations (R0, control) and 6% garcinia leaf meal in rations which were fed to the birds within 1 week (R1), 3 weeks (R2), and 5 weeks (R3). Data were subjected to a Kruskal Wallis test. Results of the hedonic test showed that the inclusion of garcinia leaf meal in rations gave significant effect (P<0.05) on meat taste but not (P>0.05) on meat aroma, tenderness, color, and juiceness. Meanwhile, results of panelis assessment in the hedonic quality test showed that significant differences (P<0.05) were found in meat tenderness, taste, and juiceness. It was concluded that duck meat color was improved with the inclusion of garcinia leaf meal in rations for 1 week and meat fishy smell was reduced with the inclusion of garcinia leaf meal in rations for 3 weeks.